Estudo e desenvolvimento de arranjos de antenas de microfita para aplicação em wlan - Almeida, Josenildo Henrique Gurgel de (2019)
The growing development of engineering, especially in the area of telecommunications, increasingly requires devices with higher speed and greater bandwidth. In addition, the constant search for increasingly lighter and more flexible devices, which can mold to the antenna's contact surface, have boosted research in the area. Microfite antennas have the ability to communicate with quality with multiple devices, are simple inexpensive, lightweight, thin profile and can have high bandwidth. This work aims to study and develop microfite antenna arrangements using as substrate the fr4-epoxy, showing in detail the procedures and materials used in the project. The antennas were scaled by the resonant cavity models and the model of the transmission line in a program developed in Matlab® according to the electrical properties of the substrates. Afterwards the antennas were simulated in the HFSS® (High Frequency Structural Simulator), where the radiation diagrams, return loss, Smith chart, current density and gain were obtained. The simulated results presented satisfactory values that can be used for later manufacture. The antennas are designed for 2.4GHz, the two-way linear arrangements and four patches respectively have gain of 5.62dB and 8.22dB. The experimental data will be compared with the simulated data, and the results analyzed according to the specialized literature that support this work